Does gender affect the prognosis and risk of complications in patients with congenital heart disease in the modern era?. (1st September 2019) - D'Alto, Michele; Budts, Werner; Diller, Gerhard P.; Mulder, Barbara; Egidy Assenza, Gabriele; Oreto, Lilia; Ciliberti, Paolo; Bassareo, Pier Paolo; Gatzoulis, Michael A.; Dimopoulos, Konstantinos
Abstract: Gender differences in the outcome of acquired cardiovascular disease are well known, but available literature on the influence of gender in congenital heart disease (CHD) is limited. Registries have provided valuable, albeit at times conflicting data. Higher mortality rates have been reported in older males with CHD, while sudden cardiac death is more prevalent in young males. However, mortality around surgery for CHD is higher in girls compared to boys, likely due to smaller body size. Women are at higher risk of developing pulmonary arterial hypertension, but at lower risk of adverse aortic outcomes, even though they are less likely to receive aortic surgery. Finally, women have a lower risk of presenting with infective endocarditis compared to men. The underlying reasons for gender differences in CHD can be attributed to genetic, hormonal, behavioural and other causes. The aim of the present paper is to provide an overview of available evidence on gender differences in CHD and their impact on outcome. Highlights: Gender differences may affect outcome in congenital heart diseases. Pregnancy can impact on the well-being of patients with congenital heart diseases. Sex differences in prognosis are due to genetic, morphological, hormonal factors.